PENGARUH FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM - Pandaya Pandaya; Pujihastuti Dwi Julianti; Imam Suprapta (STIE Muhammadiyah Jakarta, 2020)
The purpose of this study was to examine the effect of fundamental factors as seen from the elements of EPS, PER, PBV, ROE, DER and DPR on Stock Return. The analytical method used is multiple linear regression analysis. This study uses 21 companies listed on the Stock Exchange Index (IDX) that are consistently included in the LQ45 index during the 2015 to 2019 period. The determination of the sample in this study uses a purposive sampling method. Based on the analysis of the research results, EPS has a significant negative effect on stock returns, PER and PBV have a significant positive effect on stock returns, ROE and DER do not have a significant effect on stock returns and DPR has a negative effect on stock returns. The coefficient of determination from the research results of the six variables on Stock Returns is 57.0424% while the remaining 42.9576% is influenced by other factors that are not included in the research model.